1996
DOI: 10.1093/hmg/5.12.1851
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, mapping and RNA analysis of the human methionine synthase gene

Abstract: Elevated levels of plasma homocysteine is a risk factor in both birth defects and vascular disease. Methionine synthase (MS) is a cobalamin dependent enzyme which catalyzes methylation of homocysteine to methionine. Impaired MS activity is expected to lead to increased levels of plasma homocysteine. In addition, defects in this gene may underlie the methionine-dependence observed in a number of human tumor cell lines. We describe here the isolation and characterization of the human MS cDNA. It contains an open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(67 citation statements)
references
References 29 publications
0
64
0
Order By: Relevance
“…To date, studies have shown that the dysfunctional mutations in the MTR gene contribute to an elevation of plasma homocysteine levels as a consequence of altered folate metabolism and that defects in MTR activity may be important in tumorigenesis (33). Under these circumstances, DNA synthesis may be disturbed by a dysfunctional mutation in the MTR and MTRR genes by means of affecting transformation of 5-methyltetrahydrofolate to 5,10-methylenetetrahydrofolate, leading to altered DNA repair.…”
Section: Discussionmentioning
confidence: 99%
“…To date, studies have shown that the dysfunctional mutations in the MTR gene contribute to an elevation of plasma homocysteine levels as a consequence of altered folate metabolism and that defects in MTR activity may be important in tumorigenesis (33). Under these circumstances, DNA synthesis may be disturbed by a dysfunctional mutation in the MTR and MTRR genes by means of affecting transformation of 5-methyltetrahydrofolate to 5,10-methylenetetrahydrofolate, leading to altered DNA repair.…”
Section: Discussionmentioning
confidence: 99%
“…The two RNA bands that hybridize to the methionine synthase probe have been observed previously (9,ll). The shorter cDNA has been sequenced completely (9). The 10 kb band is apparently a preprocessed form of the 7.5 kb message, since it hybridizes to a probe complementary to intron 5 (11).…”
Section: 5mentioning
confidence: 99%
“…We examined MS protein levels by Western analysis. The antiserum was generated against purified porcine MS, but it cross-reacts with human, mouse, and Escherichia coli MS due to the high degree of evolutionary conservation of the MS protein (21). Among the 14 cell lines, we saw no significant difference in steadystate MS levels, with one exception (Fig.…”
Section: Ms Protein Expression and Mutation Analysismentioning
confidence: 92%